The influence of maturity status on muscle architecture in school-aged boys - Radnor, J. M.; Oliver, J. L.; Waugh, C. W.; Myer, G. D.; Lloyd, R. S. (Pediatric Exercise Science, 2020)
Purpose: To determine the differences in muscle architecture of the lower limb in pre-peak height velocity (PHV), circa-PHV, and post-PHV boys. Method: Muscle architecture variables from both the gastrocnemius medialis (GM) and vastus lateralis (VL) were derived from ultrasonographic images in 126 school-aged boys. One-way analysis of variance using Bonferroni post hoc comparisons was employed to determine between-group differences, and effect sizes were calculated to establish the magnitude of these differences. Results: All muscle architecture variables showed significant small to large increases from pre-PHV to post-PHV, excluding GM fascicle length (d = 0.59-1.39; P < .05). More discrete between-group differences were evident as GM and VL muscle thickness, and physiological thickness significantly increased between pre-PHV and circa-PHV (d > 0.57; P < .05); however, only the VL muscle thickness and physiological thickness increased from circa-PHV to post-PHV (d = 0.68; P < .05). The post-PHV group also showed larger GM pennation angles than the circa-PHV group (d = 0.59; P < .05). Conclusion: The combined results showed that maturation is associated with changes in muscle morphology. These data quantify that the maturity-related changes in muscle architecture variables provide a reference to differentiate between training-induced adaptations versus changes associated with normal growth and maturation.